The mechanisms of a bifunctional fluorescent probe for detecting fluoride and sulfite based on excited-state intramolecular proton transfer and intramolecular charge transfer - Xueli Jia; Yonggang Yang; Hongsheng Zhai; Qingqing Zhang; Yuanyuan He; Yang Liu; Yufang Liu (Structural Dynamics, 2021)
The mechanisms of 2-(Benzo[d]thiazol-2-yl)phenol-based bifunctional probe (HBT-FS) for detecting fluoride (F−) and sulfite (SO32–) based on excited-state intramolecular proton transfer (ESIPT) and intramolecular charge transfer (ICT) have been theoretically studied. Laplacian bond order of HBT-FS indicates that the F− ion cleaves the Si-O bond and then forms Compound 2 possessing a six-membered ring with a hydrogen bond. Potential energy curves and dynamic simulations confirm that ESIPT in Compound 2 occurs along with this hydrogen bond and forms a keto structure with an emission at 623 nm, which agrees with the observed experimental value (634 nm) after adding F−. Therefore, the fluorescence red-shift (from 498  to 634 nm) of HBT-FS observed in experiment after adding F− is caused by ESIPT. The SO32– ion is added to the C5 site of HBT-FS, which is confirmed by orbital-weighted dual descriptor, and then forms Compound 3 with fluorescence located at 404 nm. The experimentally measured fluorescence at 371 nm after adding SO32– is assigned to Compound 3. Charge transfer analyses indicate that the ICT extent of Compound 3 is relatively weak compared with that of HBT-FS because of the destruction of the conjugated structure by the addition reaction of SO32–, which induces the blue-shift of the fluorescence of HBT-FS from 498 to 371 nm. The different fluorescence responses make HBT-FS a fluorescent probe to discriminatorily detect F− and SO32–.